New scheme to produce aneutronic fusion reactions by laser-accelerated ions. (4th March 2015) - Baccou, C.; Depierreux, S.; Yahia, V.; Neuville, C.; Goyon, C.; De Angelis, R.; Consoli, F.; Ducret, J.E.; Boutoux, G.; Rafelski, J.; Labaune, C.
Abstract: The development of high-intensity lasers has opened the field of nuclear reactions initiated by laser-accelerated particles. One possible application is the production of aneutronic fusion reactions for clean fusion energy production. We propose an innovative scheme based on the use of two targets and present the first results obtained with the ELFIE facility (at the LULI Laboratory) for the proton–boron-11 (p– 11 B) fusion reaction. A proton beam, accelerated by the Target Normal Sheat Acceleration mechanism using a short laser pulse (12 J, 350 fs, 1.056 µm, 10 19 W cm −2 ), is sent onto a boron target to initiate fusion reactions. The number of reactions is measured with particle diagnostics such as CR39 track-detectors, active nuclear diagnostic, Thomson Parabola, magnetic spectrometer, and time-of-flight detectors that collect the fusion products: the α -particles. Our experiment shows promising results for this scheme. In the present paper, we discuss its principle and advantages compared with another scheme that uses a single target and heating mechanisms directly with photons to initiate the same p– 11 B fusion reaction.